'So why didn't you think this baby was ill?' Decision-making in acute paediatrics. Issue 1 (1st March 2018) - Roland, Damian; Snelson, Edward
Abstract : Determining severity of illness and undertaking an adequate risk assessment is a fundamental part of acute paediatric practice. This review highlights physiology, communication, heuristics and external elements as factors which influence decision-making and discusses how incidence of disease and seniority of clinician impact might influence outcomes.